Electronic counseling appointment system (e-CAPS) using round robin scheduling technique / Norhayati Romeli - Romeli, Norhayati (2014)
Balance of workload distribution among the employee or machine in an organization was an effective management and this can help an organization by having a good work schedule. This project focuses on developing a system that can auto assign counselor to the counseling appointment that has been request by client. The significance of this project is to enhance the management of counseling appointment request. The objective of this project is to solve unbalance workload at UiTM (PERAK) Counseling Unit and to build an auto assign of counselor by using the method of Round Robin Scheduling Technique. To ensure the capability of this project, the testing process has been conducted at the Counseling Unit and Kolej Anggerik I of UiTM (PERAK). Thus, the effectiveness of this project also has been evaluated through the distributed questionnaires. From the evaluation of survey, it shows that the project objectives were successfully achieved. Then, result of survey shows that 100% of the respondence had agreed to use e-CAPS as the counseling appointment system. The result also shows that 100% of the counselors and 86.66% of the students had agreed with the auto select of counselor for the appointment request. As a conclusion, the system is able to give balance to the total appointment assigned time among the counselors by using the Round Robin scheduling technique. For the future work e-CAPS was proposed to be enhance with expansion of KRS and Seminar module. Then, e-CAPS also can be added with chat room or forum as the discussion room. Lastly, e-CAPS was suggested to be integrate with SIMS and iStaf portal in order to retrieved the student and staff information.